Interactive Powerpoint Multimedia to Improve Letter Recognition Skills in Group B Children - Gusti Ayu Putu Meli Handayani; Didith Pramuditya Ambara; Ni Wayan Suniasih (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Teachers solely rely on textbooks and lecture methods in teaching. This makes students feel less engaged and bored in learning, thus hindering children's letter recognition abilities from reaching their maximum potential. This research aims to develop interactive PowerPoint multimedia to enhance letter recognition abilities in Group B children. The research adopts a development research design. The ADDIE model is utilized in the development process. Data collection methods include observation, interviews, and questionnaires. Data collection instruments consist of questionnaires and observation sheets. Data analysis employs quantitative analysis and sample-dependent t-test techniques. The study involves 24 children from Group B. The results reveal expert assessments on design at 90% (excellent category), learning content at 91.6% (excellent category), instructional design experts at 96.87% (excellent category), multimedia experts at 93.75% (excellent category), individual trials at 93.33% (excellent category), and small group trials at 92.70% (excellent category). The effectiveness test of the interactive PowerPoint multimedia yields tvalue = 13.948 > ttable = 2.069, thus rejecting H0 and accepting H1 because the post-test score is higher than the pre-test score. Consequently, it can be concluded that the use of interactive PowerPoint multimedia effectively enhances letter recognition abilities in Group B children. The implication of this research is that interactive PowerPoint multimedia can develop letter recognition abilities for Group B children.